คุณภาพชีวิตของผู้ป่วยไตวายเรื้อรังระยะสุดท้าย - ยุวดี ธีระศิลป์ (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
This study was a cross-sectional descriptive study. The purposes of this study were to investigate the quality of life among patients with end-stage renal disease and to explore factors related to the quality of life; age, gender, marital status, education level, occupation, income, medical expense reimbursement, family role, treatment mode, complications of treatment, co-morbid disease, and treatment duration. The subjects of the study consisted of 230 end-stage renal disease patients treated at King Chulalongkorn Memorial Hospital during the period from November, 2004 to February, 2005. The instrument for collecting data was the WHOQOLBREF-THAI questionnaire. The statistics utilized in this study were percent, mean, standard deviation, Chi-square, One-way ANOVA, Stepwise multiple regression analysis, and Pearsons Correlation Coefficient. Results were as follows: 1) The overall quality of life of the end-stage renal disease patients was at moderate level ( 49.1% ). Their quality of life in physical, psychological, social relationships and environment aspects were also at moderate level ( 35.2%, 36.5%, 40.9% and 40.9% respectively ). 2) The chi-square test revealed that age, marital status, education level, treatment mode, and complications of treatment were associated with the overall quality of life. 3) The three predictive factors ( p < .05 ) of the overall quality of life were educational level, treatment mode, and complications of treatment ( R[subscript 2] = 0.197 ).